2023
DOI: 10.1186/s12938-023-01066-2
|View full text |Cite
|
Sign up to set email alerts
|

The development of a home-based technology to improve gait in people with Parkinson's disease: a feasibility study

Abstract: Background People with Parkinson’s disease (PwP) may experience gait impairment and freezing of gait (FOG), a major cause of falls. External cueing, including visual (e.g., spaced lines on the floor) and auditory (e.g., rhythmic metronome beats) stimuli, are considered effective in alleviating mobility deficits and FOG. Currently, there is a need for a technology that delivers automatic, individually adjusted cues in the homes of PwP. The aims of this feasibility study were to describe the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…On the other hand, some investigations use Computer Vision techniques [ 56 , 57 , 58 , 59 , 60 ], while others have gone a step further and implement robots equipped with cameras and/or sensors. In the study described in [ 56 ], a person performs three types of exercises, and it is recorded by a camera located in a robot that follows a rectilinear trajectory, but the results are not correlated with any of the previously exposed tests, and many parameters of interest are not measured.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some investigations use Computer Vision techniques [ 56 , 57 , 58 , 59 , 60 ], while others have gone a step further and implement robots equipped with cameras and/or sensors. In the study described in [ 56 ], a person performs three types of exercises, and it is recorded by a camera located in a robot that follows a rectilinear trajectory, but the results are not correlated with any of the previously exposed tests, and many parameters of interest are not measured.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of patients undergoing DBS surgery have revealed how synchronized oscillatory activity across the cortico-basal ganglia circuit can contribute to gait kinematics and motoric impairments in PD [8][9][10][11] . For example, it has been shown that excessive STN activity at beta frequencies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which is traditionally thought to be related to both bradykinesia and rigidity, can also precede paroxysmal episodes of freezing of gait (FOG). Consistent with this observation is the finding that both motor cortical and STN beta activity display gait phase-locked modulations during walking 9 .…”
Section: Introductionmentioning
confidence: 99%
“…One way of improving gait coordination in PD is to present rhythmic visual or auditory cues during stepping [12][13][14][15] . Auditory cueing may enhance both walking speed and stride length, in addition to ameliorating FOG episodes [14][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation